Analisis Rasio Laporan Realisasi Anggaran 2010 Kota Tangerang Selatan - Udin Saefudin (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2012)
The research aims to know financial ratio District Government of Tangerang Selatan from the budget realization report, there are two financial ratios as analysis. Revenue analysis could count growth revenue and tax. To count financial ratio (district self-ratio, decentralization grade, effectiveness to revenue ratio, efficiency ratio to PAD. And expenditure analysis to know value for money (expenditure growth analysis, Operational expense to total expense, capital expenditure to total expenditure, and expenditure realization to total expenditure).